REMOTELY CONTROLLED CAR SPEED GOVERNOR - ALONGE OLUWASANMI IYIOLA; ABIOLA OLURANTI ADETUNJI; OKEDIJI ADEBUNMI PETER; ALABI ISMAILA OLANREWAJU (Journal of Engineering Studies and Research)
This study modifies a car speed limiting device with a view to avoiding car over speeding. The speed limiter was modified by incorporating a carrier chip to coordinate the activities of the speed limiter. When the car speed exceeded the designed speed limit, the speed governor came into action and restricted the car from going beyond the pre-set speed by actuating the relay. Warning signal in the form of alarm was activated, and the receiver sent a message to the owner. The study concluded that the modified speed governor design is better, safer and remotely controlled compared to the existing design.